ANALYSIS OF ABILITY OF BIOLOGICAL EDUCATION ALUMNI IN MANAGEMENT AND IMPLEMENTATION BIOLOGY PRACTICUM - Nursalmi Mahdi; Samsul Kamal; Elita Agustina; Eva Nauli Taib (Universitas Islam Negeri Ar-Raniry, 2021)
This research is motivated by efforts to improve the quality of graduates of the Biology Education Departement in the management and implementation of practicum in schools. The purpose of this research is to describe the ability of PBL alumni teachers in managing and implementing practicum. The method used is descriptive qualitative and quantitative which provides a careful description of the alumni's ability to manage and carry out practicum. The steps of data collection were questionnaires, observations and documentation studies. The technique used to analyze the data is a descriptive technique with percentages. The results of the study on the ability of the alumni of the Biology Education Study Program in managing practicum showed the following: (1) The planning of the laboratory work program (53.33%) was declared good; (2) Laboratory organization was stated to be very good (33.33%) (3) The implementation of the laboratory work program (46.66%) was stated to be very good; and (4) the supervision and evaluation of the laboratory work program (26.66%) was stated to be very good. While the ability of alumni teachers in carrying out practicum is in the good category (75.3%). Teachers play an important role in the management and implementation of effective practicum